SIMULATION MODELING OF CONGESTION IN TELECOMMUNICATION SYSTEMS TO DETERMINE THE OPTIMAL PARAMETERS OF LINEAR NETWORK CODE - Karpukhin, Eugene; Meshavkin, Konstantin; Britvin, Nikita (Revista Inclusiones, 2020)
Simulink software environment is used as a tool for simulating congestion in networks that arise due to the presence of a “bottleneck” in the data transmission channel or the attacker's influence on the telecommunication system. The structure and functioning principle of the developed simulation model, as well as the data upload mechanism for their further use in determining the optimal parameters of a linear network code are described. A feature of the model is the implementation of the random early detection (RED) algorithm in it for queuing in its device, which simulates the “bottleneck”. Three cases were selected for modeling: load insufficient for serious losses, load close to maximum and load exceeding the capacity of the “bottleneck”. Based on the simulation modeling results, the average packet loss values are obtained and the data are downloaded in the form of text files. These data were transmitted as input parameters of the model, which determines the optimal parameters of the network code by the nature of packet losses in the downloaded text files. Linear network code parameters that are optimized include the length of the code sequence and the corrective ability of the code. The model estimates the probability of packet loss and calculates the code speed depending on the length of the code sequence and it’s correcting ability.